2021
DOI: 10.37715/jaef.v3i1.2231
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Financial Performance of Ceramic, Porcelain, and Glass Sub-Sector Industries

Abstract: One of basic industrial and chemical companies listed on the Indonesia Stock Exchange (IDX is the ceramic, porcelain and glass sub-sector industry. The large number of imported ceramics from China and India has resulted in intense competition between local and imported products. This is also marked by the existence of a government regulation to reduce the number of imported products in Indonesia by increasing 10% tax on imported ceramics. The intense competition can result local products being unable to compet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The two traditional liquidity ratios follow the importance of margin ratios, emphasizing the necessity of possessing adequate current assets to meet short-term liabilities. The significance of these ratios has been acknowledged in several previous studies, including those conducted by Kurniawandi (2021) and Muthu and Wesson (2023).…”
Section: Results Of Examining H3mentioning
confidence: 86%
See 1 more Smart Citation
“…The two traditional liquidity ratios follow the importance of margin ratios, emphasizing the necessity of possessing adequate current assets to meet short-term liabilities. The significance of these ratios has been acknowledged in several previous studies, including those conducted by Kurniawandi (2021) and Muthu and Wesson (2023).…”
Section: Results Of Examining H3mentioning
confidence: 86%
“…After analyzing the financial performance of Saudi Arabian companies in the manufacturing and insurance sectors, Rahman and Sharma (2020) came to the conclusion that size, leverage, operating cash flow, and industrial membership had a significant impact on financial performance. The best predictor ratios were cash turnover, asset turnover, and current ratio, according to Kurniawandi's (2021) research on the drivers of market book value (MBV) and return on assets (ROA) in three Indonesian sectors. Similar research by Wira (2021) showed that net profit margins, accounts receivable turnover rates, and debt ratios all significantly impacted firm value.…”
Section: Financial Performance-related Publications In the Fieldmentioning
confidence: 99%